Impact of Psychometrically Defined Deficits of Executive Functioning in Adults With Attention Deficit Hyperactivity Disorder - Biederman, Joseph; Petty, Carter; Fried, Ronna; Fontanella, Jessie; Doyle, Alysa E.; Seidman, Larry J.; Faraone, Stephen V. (The American journal of psychiatry, 2006)
Objective: The association between deficits in executive functioning and functional outcomes was examined among adults with attention deficit hyperactivity disorder (ADHD). Method: Subjects were adults who did (N=213) and did not (N=145) meet DSM-IV criteria for ADHD. The authors defined having deficits in executive functioning as having at least two measures of executive functioning with scores 1.5 standard deviations below those of matched comparison subjects. Results: Significantly more adults with ADHD had deficits of executive functioning than comparison subjects. Deficits of executive functioning were associated with lower academic achievement, irrespective of ADHD status. Subjects with ADHD with deficits of executive functioning had a significantly lower socioeconomic status and a significant functional morbidity beyond the diagnosis of ADHD alone. Conclusions: Psychometrically defined deficits of executive functioning may help identify a subgroup of adults with ADHD at high risk for occupational and academic underachievement. More efforts are needed to identify cost-effective approaches to screen individuals with ADHD for deficits of executive functioning.